Mercury removal from wastewater using palm oil fuel ash - Imla Syafiqah, Mohd Salleh; Nor Akmalina, Mustazar; Hafizuddin, Wan Yussof (EDP Sciences, 2018)
Palm oil fuel ashes (POFA) were used as the adsorbents for the removal of Hg II) ions from wastewater. From the preliminary experimental results, it shows that the POFA had good adsorption capability for Hg (II) ions. Initially, five factors were screened using 25-1 factorial analysis in batch mode. From these factors, only two of them gave the significant effect which are contact time and agitation speed. Both also have obtained a maximum point which is likely to be the optimum point and possible for the optimization process. This study aims to optimize these two variables (contact time and agitation speed) using central composite design (CCD) which is a subset of response surface methodology (RSM). Quadratic model was developed for Hg (II) percentage removals. A 22 factorial CCD was used to get the mutual interaction between variables. The optimum adsorption conditions were obtained at contact time of 5 hr and agitation speed of 150 rpm with desirability of 0.95. At these optimum points, the mercury removal efficiency was calculated at 98.93 %. Based on the predicted and experimental results presented, the experimental values were in good agreement with the predicted values proposed by the model with an error less than 5 % and proved to be an adequate model. The results indicated that POFA has the potential to be used as an adsorbent for the removal of Hg (II) from aqueous environments due to its significant adsorption capacity and naturally abundance at low cost value.